Funcionamiento familiar autoestima y consumo de alcohol y tabaco. Institución Educativa 80706 Alto Moche 2012 - Cobian Becerra, Yessica Milagros (2013)
This cross-sectional descriptive quantitative research was performed from November to December 2012, in 80706 High School, in order to determine the relationship between, self-esteem levels, family functioning and, snuff and alcohol consumption in teenagers. The universe consisted of 177 people, of which 30 were chosen for the sample, according to established inclusion criteria. For data collection we used the Coopersmith self esteem test and scale Olson Family Functioning. Data were tabulated and presented in statistical tables of single and double entry. The analysis of the relationship between the study variables was performed by Chi square test (X2). In the discussion of the results we concluded that:The 1.7 percent have low family functioning, the 7.9 percent median family functioning and family functioning 90.4 percent higher. 4.6 percent have low self-esteem, 19.1 percent lower middle level of self-esteem, the 53.4 percent upper middle level of selfesteem and the 90.4 percent level of high self-esteem.The 50.8 percent did not consume alcohol and 49.2 percent If you consume.The 84.7 percent have not consume snuff and 15.3 percent if they consume Snuff. There is significant relationship (p = 0.0412) between the level of self-esteem and snuff consumption. The level of self-esteem and alcohol consumption has no significant relationship and family functioning has no significant relationship with alcohol and snuff.